JMP connections - Wubbel, John, 1954- (John Wiley & Sons, Inc., 2017)
Achieve best-in-class metrics and get more from your data with JMP®. JMP® Connections is the small- and medium-sized business owner's guide to exceeding customer expectations by getting more out of your data using JMP®. Uniquely bifunctional, this book is divided into two parts: the first half of the book shows you what JMP® can do for you. You'll discover how to wring every last drop of insight out of your data, and let JMP® parse reams of raw numbers into actionable insight that leads to better strategic decisions. You'll also discover why it works so well; clear explanations break down the Connectivity platform and metrics in business terms to demystify data analysis and JMP® while giving you a macro view of the benefits that come from optimal implementation. The second half of the book is for your technical team, demonstrating how to implement specific solutions relating to data set development and data virtualization. In the end, your organization reduces Full Time Equivalents while increasing productivity and competitiveness. JMP® is a powerful tool for business, but many organizations aren't even scratching the surface of what their data can do for them. This book provides the information and technical guidance your business needs to achieve more. Learn what a JMP® Connectivity Platform can do for your business Understand Metrics-on-Demand, Real-Time Metrics, and their implementation. Delve into technical implementation with information on configuration and management, version control, data visualization, and more. Make better business decisions by getting more and better information from your data Business leadership relies on good information to make good business decisions--but what if you could increase the quality of the information you receive, while getting more of what you want to know and less of what you don't need to know? How would that affect strategy, operations, customer experience, and other critical areas? JMP® can help with that, and JMP® Connections provides real, actionable guidance on getting more out of JMP®.